Pengaruh Nilai Perusahaan, Pertumbuhan Aset dan Leverage terhadap Profitabilitas - Febrian, Gerry (Journal of Innovation in Management, Accounting and Business, 2025)
This study analyzes the effect of firm value, asset growth, and leverage on the profitability of companies in the property and real estate sector listed on the Indonesia Stock Exchange (IDX) for the 2019-2023 period. The method used is a quantitative approach with panel regression analysis techniques using EViews 12 software. The research sample consists of 30 companies selected through purposive sampling technique. The results showed that firm value has no significant effect on profitability, which indicates that investors focus more on growth prospects than current profits. In contrast, asset growth has a positive and significant effect on profitability, which confirms that increasing assets can increase the company's operational capacity and its revenue. Leverage also has a positive effect on profitability, suggesting that optimal use of debt can increase corporate profits through tax efficiency and expansion funding. These results provide insight for company management in managing financial strategies to increase profitability Keywords: firm value, asset growth, leverage, profitability